Peningkatan Literasi Siswa SD Negeri 106204 Tanjung Raja Melalui Pojok Baca - Hendra; Nuri Ramadhan; Leni Malinda; Emy Hariati; Sisilia Florina Yanti; Nurbaity Situmorang; Dewi Novina Sukapiring; Hendri Irawan; Muhammad Khaibar Putra Adhitia; Nurul Ajima Ritonga; Astria Ayu Ramadianti; Syarifah Ainun Harahap (Jurnal Pengabdian Masyarakat, 2023)
With children's interest in reading still low, the government launched the School Literacy Movement (GLS). This program is expected to foster interest in reading in students as well as to build a literacy climate in schools. However, not all schools have been able to implement GLS in accordance with the guidelines provided. The problems include inadequate facilities and infrastructure, limited reading materials, limited reading time. The purpose of this community service is to develop reading literacy in students at UPT Elementary School in launching GLS through books and reading trees provided by the PKM team to each partner school. Activities in assisting the making of this class reading corner are carried out by the team and class teachers at the State Elementary School, starting from preparing the class that will later be made a class reading corner, the materials needed in making the reading corner, the books to be donated, and the teacher's role in mentoring later. The team will also donate basic education level books and folklore books to fulfill the bookshelves that will be made in the reading corner later. The end result of this activity is expected that the reading corner that has been made will be emulated by teachers in other classes and the donated books will be useful for teachers and students and schools.